Knowledge and attitudes of male nursing students towards male breast cancer and breast self-examination: An example from Turkish society - Saritas, Serdar; Aslan Dogan, Bahar; Gul, Ebru (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the knowledge and attitudes of male nursing students on male breast cancer and male breast self-examination.Material and Methods: This descriptive was conducted with 490 students studying in the faculty of nursing at a university in Malatya, Turkey. The research was completed with 307 male students. Data were collected using a participant identification form and questionnaire form which was developed by the researchers. The results were expressed as number, percentage, mean and standard deviation. Results: It has been determined that 83.4% of the students know that breast cancer can be seen in males, 72% and 67% were previously informed about male breast cancer and breast self-examination, respectively. In addition, it was found that 83.7% of the students have never performed breast self-examination, 82.1% know that breast cancer is rare in males and 88.3% know that early diagnosis of breast cancer is of important. 27.4% of the students stated that male breast cancer does not consider going to the doctor because it is a rare disease. 33.2 % also stated that they regard breast self-examination as a boring process.Conclusion: It was determined that male nursing students have substantial knowledge about male breast cancer, more than half of them answered the questions about the literature on this subject correctly, but their attitude toward breast self-examination should be developed.